(untitled) (Metallurgy and Foundry Engineering, 2017)
The problem of the disposal of metallurgical slags in the copper-nickel industry also remains open in the Kola Peninsula area, where this kind of exploitation and processing of sulphide Cu-Ni deposits is conducted. The urgent need is to reuse the waste slag heaps through the effective manner of their use based on our available technologies. The slag obtained after processing sulphide copper-nickel ores in the Kola Peninsula contains about 4 wt.% of the ore. The chemical and mineral composition of the slag plays a key role when considering the possibility of its re-use in the context of environmental nuisance. The line of processing Cu-Ni sulfide deposits from the slag proposed by the authors is based on the ability to change the slag phase composition by its oxidation and reduction processes for the enrichment of ore mineralization for reuse.